2020
DOI: 10.1097/mou.0000000000000808
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of severe acute respiratory syndrome coronavirus 2 in urine

Abstract: Purpose of review Despite the plethora of publications discussing the severe respiratory coronavirus 2 (SARS-CoV-2), evidence of viral secretion in urine is sparse. Recent findings We could identify 34 publications including a total of 2172 patients. Among those, 549 patients were tested for SARS-CoV-2 secretion in urine, which was detected in only 38 patients (6.9%). Within the seven studies displaying positive results, the majority of positive patients (86.8%) was from not yet peer-reviewed studies including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Few studies have reported virus isolation from urine samples of patients with severe COVID‐19, most of which including weak data and various techniques for sample urine testing 24,31,32 . A systematic review on COVID‐19 reported a pool of 11 studies with patients who had their urine tested with RT‐PCR for viral RNA.…”
Section: Considerations Of Sars‐cov‐2 and The Urinary Tractmentioning
confidence: 99%
“…Few studies have reported virus isolation from urine samples of patients with severe COVID‐19, most of which including weak data and various techniques for sample urine testing 24,31,32 . A systematic review on COVID‐19 reported a pool of 11 studies with patients who had their urine tested with RT‐PCR for viral RNA.…”
Section: Considerations Of Sars‐cov‐2 and The Urinary Tractmentioning
confidence: 99%
“…Although SARS-CoV-2 has been shown to shed in the upper respiratory tract, the lower respiratory tract, feces, urine and serum (Cevik et al, 2020), WBE leverages RNA shedding of SARS-CoV-2 in feces. Infected persons shed virus into sewage via feces (Cevik et al, 2020), or urine (Brönimann et al, 2020), both of which can then be used to monitor population-level infection changes. Although SARS-CoV-2 has been isolated in urine of a COVID-19 patient (Sun et al, 2020), the incidence of the virus in urine is reported to be low (Brönimann et al, 2020;Morone et al, 2020); whereas, intact SARS-CoV-2 virus have been isolated from feces (Wang et al, 2020;Xiao et al, 2020;Zhang et al, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…Putting all these factors together, these data led to the hypothesis that SARS-CoV-2 targets the kidney. This hypothesis was compounded by data regarding the presence of messenger ribonucleic acid (mRNA) and virus in the kidney tissue [ 14 ▪▪ ], electron microscopy data indicated COVID-19 could be associated with tissue damage [ 15 ▪ ], and evidence of SARS-CoV-2 mRNA was to be found in the patients’ urine [ 4 ▪ , 16 , 17 ]. Moreover, one of the first papers on the topic even suggested that we may observe radiological changes in the kidneys.…”
Section: Recent Findingsmentioning
confidence: 99%
“…A large number of studies suggest that the presence of ACE-2 receptors in the kidneys would appear to be the main reason for acute kidney injury (AKI) in patients with SARS-CoV-2 [ 2 ]. These data followed by the reports suggesting that the viral ribonucleic acid (RNA) may be isolated from urine [ 3 ] has ignited debates regarding the rate SARS-CoV-2 secretion and virulence in urine [ 4 ▪ ]. The available data on the effect of SARS-CoV-2 on the kidney and urinary system are inconsistent suggesting an AKI rate in 0.1–29% of patients [ 5 , 6 ▪ ].…”
Section: Introductionmentioning
confidence: 99%